The effect of thermo-mechanical loading on fracture-related parameters of austenitic steel; Engineering Failure Analysis; Vol. 81 - Lyubimova L. L. Lyudmila Leonidovna; Tashlykov A. A. Aleksandr Anatolievich; Tabakaev R. B. Roman Borisovich; Levin A. A. Aleksandr Andreevich; Popov A. Yu. Aleksey Yurjevich (2017, 2017)
Title screen